PROSES PENYULUHAN AGAMA HINDU DI SATUAN KERJA PERANGKAT DAERAH PROVINSI NTB - Sutama, I Wayan (Widya Sandhi, 2018)
Religious counseling is a form of unit activities that have strategic value, especially in carrying out of functions of the expedite implementation development in the field of religion. Religious counseling of Hinduism is in fact a process of education that aims to enhance the awareness and behavior (knowledge, attitude and skill) communities into a better direction. Descriptive research method is used in this research. Theoretical basic are SMCRE theory, the theory of innovation and the theory of rasa. The technique of data collection in this research is survey method, observation, in-depth interviews and documentation. The results of research discover that process counseling of Hinduism is moderator opening the event, introduced the counselor and the message to be conveyed. Than counselor the convey the message of Dharma Wacana method for 15 minutes. Moderator guides the discussion (Dharma Tula) for 40 minutes related to the message presented by give the participants an opportunity to ask or give feedback. Next counselor is given the opportunity to answer or provide clarification on questions and responses of participants